Macroeconomic Effects of Political Regime Type in African Sub-Regions - Fanny, Kabwe Omoyi (Asian Journal of Economic Modelling, 2021)
This paper is to empirically examine the effects of type of political regime on economic growth in a context of African Sub-Regions. Among the political determinants of the institutional environment, democracy as a Polity IV indicator is seen as contributing to stronger economic performance. We using a sample of panel data from 45 African countries over the period 1991 to 2019, employs GMM difference regression. First, the results show that the type of political regime (especially democracy) improves economic performance (i.e. a one-point change in democracy increases economic performance by 63.4% in Central Africa, by 15.1% in Southern Africa, by 41.5% in East Africa). Second, the policy recommendations that flow from the findings are as follows: put education sector promotion issues at the heart of government strategies and therefore make it a priority; regional integration can serve as a "development" obligation that generates economic development and political stability.